Soluble IGF2 receptor rescues Apc(Min/+) intestinal adenoma progression induced by Igf2 loss of imprinting. - Harper, J; Burns, J; Foulstone, E; Pignatelli, M; Zaina, S; Hassan, A (2006)
The potent growth-promoting activity of insulin-like growth factor-II (IGF-II) is highly regulated during development but frequently up-regulated in tumors. Increased expression of the normally monoallelic (paternally expressed) mouse (Igf2) and human (IGF2) genes modify progression of intestinal adenoma in the Apc(Min/+) mouse and correlate with a high relative risk of human colorectal cancer susceptibility, respectively. We examined the functional consequence of Igf2 allelic dosage (null, monoallelic, and biallelic) on intestinal adenoma development in the Apc(Min/+) by breeding with mice with either disruption of Igf2 paternal allele or H19 maternal allele and used these models to evaluate an IGF-II-specific therapeutic intervention. Increased allelic Igf2 expression led to elongation of intestinal crypts, increased adenoma growth independent of systemic growth, and increased adenoma nuclear beta-catenin staining. By introducing a transgene expressing a soluble form of the full-length IGF-II/mannose 6-phosphate receptor (sIGF2R) in the intestine, which acts as a specific inhibitor of IGF-II ligand bioavailability (ligand trap), we show rescue of the Igf2-dependent intestinal and adenoma phenotype. This evidence shows the functional potency of allelic dosage of an epigenetically regulated gene in cancer and supports the application of an IGF-II ligand-specific therapeutic intervention in colorectal cancer.